Ресурси як основа забезпечення адаптивності діяльності підприємства - Османова, З.О. (Культура народов Причерноморья, 2013)
В статье исследовано обеспечения адаптивности деятельности предприятия. В качестве средства обеспечения адаптивности деятельности предприятия выбраны ресурсы предприятия (основные производственные фонды, финансовые и материальные ресурсы, носители знаний, информационные и нематериальные ресурсы) и их резервы. По разработанным признакам проведена классификация обеспечения адаптивности деятельности предприятия и охарактеризованы виды обеспечения адаптивности деятельности предприятия в рамках представленной классификации. В статті досліджено забезпечення адаптивності діяльності підприємства. В якості засобу забезпечення адаптивності діяльності підприємства обрано ресурси підприємства (основні виробничі фонди, фінансові та матеріальні ресурси, носії знань, інформаційні та нематеріальні ресурси) та їхні резерви. За розробленими ознаками проведена класифікація забезпечення адаптивності діяльності підприємства та охарактеризовано види забезпечення адаптивності діяльності підприємства в межах представленої класифікації. Systematic changes of environmental conditions require from the enterprise permanent reaction from them, because adaptation is a condition of adaptation of an enterprise to the conditions of environment, research issues to ensure its take on special importance. The adaptability frequently examined in modern scientific works as a subject of research in a specific subject. Questions of the role and place of adaptations in the adaptability of an enterprise to environmental conditions and in the enterprice's activity as a whole a little known. In the article providing adaptability of an enterprice's activity was examined. The analysis of classification of enterprise resources were done. The enterprice's resources and their reserves were chosen as a means of providing adaptability of an enterprice's activity (basical production funds, financial and material resources, the career of knowledge, information and non–material resources). The role of reserves in the providing of adaptability of an enterprice's activity were characterized. The classification of maintenance adaptability of an enterprice's activity according to the elaborated properties was held and kinds of maintenance of adaptability of an enterprice's activity were characterized according to this classification. Classifications of providing adaptability of an enterprice's activity was held by goals, source of formation, shape, level, time, efficiency and by types of resources which are used. Evidence of providing adaptability of an enterprice's activity and types of providing in this classification, which dependence from the purpose of the studing can be extended.